PELAKSANAAN DESENTRALISASI DAN OTONOMI DAERAH BERDASARKAN U.U. NO. 32 TAHUN 2004 - SANTOSO BUDI N (Wacana Hukum, 2010)
Abstract:In order to establish the local autonomy government, the integration of decentralization, deconcentration and supporting task are needed. Focusing on the establishment of the function and the role of Governor as the government representation, it organizes and coordinates between central and local government and also guides and supervises the process of good corporate government within the provincial and district area. Keywords: Decentralisation, Local autonomy.